MEASURING OVERCONSUMPTION: DEVELOPMENT AND VALIDATION OF A SCALE FOR GENERATION Y IN THAILAND - CHINDA, Mantita; TAIPHAPOON, Tatri (Asian Administration and Management Review, 2025)
This study aims to develop and validate a scale to measure overconsumption among Thai Generation Y consumers, addressing the pressing issue of household debt. Drawing upon three key constructs—Impulse Buying, Compulsive Buying, and Conspicuous Consumption—the study employs a rigorous three-phase methodology with 400 participants. The initial phase involved conceptual framework development, followed by reliability testing using Cronbach’s alpha. A second-order confirmatory factor analysis (CFA) confirmed the scale's construct validity (χ²/df = 1.878, GFI = .961, CFI = .985, RMSEA = .051). Results demonstrate that the Overconsumption Scale for Generation Y possesses robust psychometric properties and is suitable for assessing overspending tendencies. This new measurement tool would serve as a valuable resource to financial institutions and governmental stakeholders interested in implementing programs to foster responsible financial conduct. The study findings are particularly relevant and timely given the economic challenges and evolving consumption patterns observed within this demographic.